2014
DOI: 10.1128/aac.02515-13
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl Isothiocyanate Inhibits Shiga Toxin Production in Enterohemorrhagic Escherichia coli by Stringent Response Induction

Abstract: bThe pathogenicity of enterohemorrhagic Escherichia coli (EHEC) depends on production of Shiga toxins, which are encoded by stx genes located in the genomes of lambdoid prophages. Efficient expression of these genes requires prophage induction and lytic development of phages. Treatment of EHEC infections is problematic due to not only the resistance of various strains to antibiotics but also the fact that many antibiotics cause prophage induction, thus resulting in high-level expression of stx genes. Here we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 61 publications
(89 reference statements)
6
48
0
Order By: Relevance
“…In this study, not only did the abundance of the Stx2-converting phage decrease, the total number of phage decreased proportionally with the increase of cinnamon oil concentration, which explained the reduction of Stx2 production. A similar phenomenon was observed in that subinhibitory concentrations of phenethyl isothiocyanate, which is a derivative of glucosinolate found in cruciferous vegetables, significantly reduced the amount of Stx-encoding phage and stx expression in E. coli O157:H7 (58).…”
Section: Discussionmentioning
confidence: 53%
“…In this study, not only did the abundance of the Stx2-converting phage decrease, the total number of phage decreased proportionally with the increase of cinnamon oil concentration, which explained the reduction of Stx2 production. A similar phenomenon was observed in that subinhibitory concentrations of phenethyl isothiocyanate, which is a derivative of glucosinolate found in cruciferous vegetables, significantly reduced the amount of Stx-encoding phage and stx expression in E. coli O157:H7 (58).…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, supplementation of glycine or arginine in the growth medium, thereby increasing the pool of free amino acids at inhibitory concentrations of ITC, was able to restore growth of bacterial cultures treated with PEITC and increased the MIC of PEITC for E. coli. This MIC-increasing effect was also observed by supplementing lysine, methionine, phenylalanine, serine and threonine (Nowicki et al, 2014). The antibacterial properties of isothiocyanates…”
Section: Induction Of Heat-shock and Oxidative Stress Responsesmentioning
confidence: 74%
“…Induction of a stringent response Nowicki et al (2014) have reported the efficacy of PEITC in inhibiting the growth of enterohaemorrhagic E. coli (EHEC) as well as Shiga toxin production. The authors correlated these effects to the induction of a stringent response.…”
Section: Induction Of Heat-shock and Oxidative Stress Responsesmentioning
confidence: 99%
“…Such factors include hydrogen peroxide (Wagner et al, 2001;Łoś et al, 2009, 2010, high temperature in combination with UV irradiation (Yue et al, 2012), EDTA (Imamovic & Muniesa, 2012), sodium citrate (Imamovic & Muniesa, 2012;Nejman-Faleń czyk et al, 2012), amino acid starvation (Nejman-Faleń czyk et al, 2012), phenethyl isothiocyanate (Nowicki et al, 2014), DNase colicins (Toshima et al, 2007), high hydrostatic pressure (Aertsen et al, 2005a), sodium chloride (Łoś et al, 2009;Harris et al, 2012), nitric oxide (Vareille et al, 2007), 60 Co irradiation (Yamamoto et al, 2003) Łoś et al, 2009;Nassar et al, 2013), as well as those antibacterials used as growth promoters in animal production (Köhler et al, 2000).…”
Section: Induction Of Stx Phagesmentioning
confidence: 99%